2020
DOI: 10.1039/d0nr05003b
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide sheets and quantum dots inhibit α-synuclein amyloid formation by different mechanisms

Abstract: Aggregation and amyloid formation of the 140-residue presynaptic and intrinsically disordered protein α-synuclein (α-syn) is a pathological hallmark of Parkinson's disease (PD). Understanding how α-syn forms amyloid fibrils, and investigations...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 72 publications
(85 reference statements)
2
28
0
Order By: Relevance
“…Therefore, GQDs have been suggested as therapeutic agents in inflammatory diseases [26]. GQDs also have protective impacts on Parkinson's disease through interaction with α-synuclein without complications [27,28]. In line with the above studies, our results demonstrated that GQDs-PEG attenuated heart injuries and improved left ventricular contractility and cardiac function after MI.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, GQDs have been suggested as therapeutic agents in inflammatory diseases [26]. GQDs also have protective impacts on Parkinson's disease through interaction with α-synuclein without complications [27,28]. In line with the above studies, our results demonstrated that GQDs-PEG attenuated heart injuries and improved left ventricular contractility and cardiac function after MI.…”
Section: Discussionsupporting
confidence: 87%
“…Recent studies have shown that GDQs themselves can also inhibit α-syn aggregation and promote disaggregation of mature fibrils ( Mohammad-Beigi et al, 2019 ). This aggregation inhibitory effect of GDQs is dependent on its surface chemistry and dimensionality, which can interfere with the rate of protein aggregation, the mechanism of inhibition, and the morphology of the aggregated products ( Ghaeidamini et al, 2020 ). The effect of GDQs was further illustrated by Kim et al (2018) .…”
Section: Promising Theranostics Nanotechnology Targeting α-Syn Aggregationmentioning
confidence: 99%
“…More specifically, graphene sheets sequester the α‐synuclein monomers, preventing primary nucleation and elongation, whereas GQDs affect the secondary formation processes. [ 88 ] Of note, the α‐synuclein aggregation inhibition is time‐ and concentration‐dependent [ 88,90 ] with low concentration to potentially enhance the aggregation phenomena. [ 88 ] In addition to the aggregation inhibition, GQDs have been shown to reduce the number of Lewy bodies and the subsequent Lewy neurite formation, bringing to inhibition of neuronal death and synaptic loss.…”
Section: Gbms In Neurodegenerative Diseasesmentioning
confidence: 99%
“…As in AD, the main therapeutic approaches for PD focus on the dissociation of formed fibrils or the fibrillation inhibition of αsynuclein. [87] To achieve this therapeutic effect, graphene sheets [88,89] and GQDs have been used. [88][89][90] These reported studies have shown that the electrostatic interactions between the negatively charged surfaces of the GBMs and the positively charged regions of α-synuclein are mainly responsible for the dissociation and the formation inhibition of fibrils.…”
Section: Graphene-based Therapeutics For Pdmentioning
confidence: 99%
See 1 more Smart Citation